Perancangan Prototype User Interface Dan Pengujian User Experience Aplikasi Rental Mobil Berbasis Menggunakan Metode Design Thinking ( Studi Kasus : Pt Trans Berjaya Khatulistiwa) - Budiman; Titan, Titan Parama Yoga; Efendi Putra, Jilan Hafizh Ferdiansyah (FKOM UNIKU, 2023)
PT Trans Berjaya Khatulistiwa or commonly called Tiketux is a travel ticket booking service company, and mobile and web application developer. Currently Tiketux is developing a web application regarding car rental, to get the results of a UI/UX design that are right on target with user needs using the design thinking method. The design stage in this method is to take an approach that does not only focus on what is seen (the user interface) and felt by the user, but also focuses on the user experience. The research method used is a mix method, namely conducting observations, distributing questionnaires, and searching for data literature through books or journals related to research. The results obtained in this car rental application have good usability for users. This can be seen from the SUS trial regarding the designed user interface prototype